2013
DOI: 10.1108/bjm-12-2012-0115
|View full text |Cite
|
Sign up to set email alerts
|

Human resource management practices and the HRM-performance link in public and private sector organizations in three Western societal clusters

Abstract: Purpose -The purpose of the paper is to explore HRM practices and HRM-performance (HRM-P) link in public and private sector organizations across three societal clusters: the Anglo, the Germanic, and the Nordic European. Design/methodology/approach -The article is based on international Cranet HRM survey data collected from large private and public organizations. Findings -According to results, HRM is more advanced in private companies than in public sector organizations, even across three societal clusters. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 95 publications
0
28
0
Order By: Relevance
“…Such environment includes many factors as increased globalization, rapid technological change, and the growing need for qualified employees and improved performance (Vanhala & Stavrou, 2013). This forces organizations to try and exploit the resources at its disposal in order to achieve a competitive advantage (Savaneviciene & Stakeviciute, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Such environment includes many factors as increased globalization, rapid technological change, and the growing need for qualified employees and improved performance (Vanhala & Stavrou, 2013). This forces organizations to try and exploit the resources at its disposal in order to achieve a competitive advantage (Savaneviciene & Stakeviciute, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The previous researches have proved that human resource management in public sector organization has the main role in performance enhancement. Vanhala & Stavrou (2013) while investigating the human resource management practices and the correlation between human resource managements and performances in the public and the private sectors among three social clusters namely Anglo (Australia, Canada, New Zealand, England, and USA), European-Germany (Austria, Germany, and Netherlands) and European-Nordic (Denmark, Norwegia, and Sweden), found correlation between human resource managements and discovered that the performances are stronger in the public sector organizations compared with the private sector organizations. Another research comes from a developing country namely Ghana which was conducted by Antwi and Analoui (2008) showed that human resource has correlation with policy, task/skill/organization, and performance motivation.…”
Section: Human Resource Capabilitymentioning
confidence: 99%
“…Also [57] argues that to achieve its full potential the Public Service must improve its ability to recruit and select staff more effectively. This means that both HR sections in departments and managers themselves must enhance their skills in performing this crucial function.…”
Section: B Theoretical and Empirical Challengesmentioning
confidence: 99%